The role of regulatory B cells in allergen immunotherapy. Issue 6 (December 2017) - van de Veen, Willem
Abstract : Purpose of review: Allergen immunotherapy (AIT) is currently the only curative treatment available for allergic diseases, and has been used in clinical practice for over a century. Induction and maintenance of immune tolerance to nonhazardous environmental and self-antigens is essential to maintain homeostasis and prevent chronic inflammation. Regulatory B (BREG ) cells are immunoregulatory cells that protect against chronic inflammatory responses primarily through production of anti-inflammatory cytokines such as IL-10, transforming growth factor-β, and IL-35. The importance of BREG cells has been extensively demonstrated in the context of autoimmune diseases. Data showing their role in the regulation of allergic responses are slowly accumulating. This review summarizes recent findings relevant to the topic of BREG cells and their potential role in AIT. Recent findings: BREG cells support AIT in models of allergic airway inflammation and intestinal inflammation through induction of regulatory T (TREG ) cells. In humans BREG frequency increases during venom immunotherapy while the phenotype of allergen-specific B cells changes. Mechanisms of BREG -mediated tolerance to allergens include IL-10-mediated suppression of effector T cell, including TH 2 responses, induction of TREG cells, IL-10-mediated inhibition of Dendritic cell maturation, modulation of T follicular helper responses, and production of anti-inflammatory IgG4 antibodies. Summary: Current evidence supports a potential role for BREG cells in induction and maintenance of allergen tolerance during AIT. A better understanding of the role of B cells and BREG cells in AIT could open potential new windows for developing targeted therapies specifically focused on promoting BREG responses during AIT.